The diagnostic value of serum 25-Hydroxyvitamin D, MIS and Insulin-like Growth Factor 1 for polycystic ovary syndrome (PCOS): Serum 25-Hydroxyvitamin D, MIS and Insulin-like Growth Factor 1 for polycystic ovary syndrome (PCOS) - Sun, Shaomeng; Zheng, Jianrui; Xie, Ziying (Journal of Medical Biochemistry, 2025)
Objective To investigate blood levels and the importance of Müllerian Inhibiting Substance (MIS), insulin-like growth factor 1 (IGF-1), insulin-like growth factor binding protein 3 (IGFBP-3), and 25-hydroxyvitamin D [25(OH)D] in patients with polycystic ovarian syndrome (PCOS). Methods The observation group consisted of 212 PCOS patients who received treatment at this institution between May 2022 and May 2024, while the control group consisted of 212 healthy women who were examined physically at same hospital within the same time frame. The two groups’ general information, serum 25(OH)D, MIS, IGF-1, and IGFBP-3 levels, as well as their sex hormones and glucose metabolism markers, were compared. PCOS patients were divided into the IR group and the non-IR group according to whether insulin resistance (IR) occurred. The two groups’ levels of serum 25(OH)D, MIS, IGF-1, and IGFBP-3 were compared. The study examined the associations among the four markers and the homeostasis model of insulin resistance index (HOMA-IR), as well as their supplementary diagnostic utility for PCOS. Results The level of 25(OH)D in the observation group was lower than that in the control group (P<0.05). Total testosterone (TT), luteinizing hormone (LH), estradiol (E2), fasting insulin (FINS), fasting blood glucose (FBG), serum MIS, IGF-1, IGFBP-3, HOMA-IR, and the average body mass index were all greater in the observation group than in the control group (P<0.05). The IR group’s 25(OH)D level was lower than the non-IR group’s (P<0.05). Serum MIS, IGF-1, and IGFBP-3 levels were higher in the IR group than in the non-IR group (P<0.05). The levels of serum MIS, IGF-1 and IGFBP-3 in the observation group were positively correlated with HOMA-IR (r=0.659, 0.586, 0.565, P<0.05), and 25(OH)D was negatively correlated with HOMA-IR (r=-0.548, P<0.05). The combined auxiliary diagnosis of PCOS by serum 25(OH)D, MIS, IGF-1, and IGFBP-3 had an area under the curve of 0.963, according to the results of receiver operating characteristic curve analysis, which was greater than that of the single detection of each index (0.819, 0.864, 0.814, 0.799). Conclusion MIS, IGF-1, IGFBP-3, and serum 25(OH)D levels are associated with the development and occurrence of PCOS. The combined detection of these four indicators has high auxiliary diagnostic value for PCOS and is conducive to clinical prevention and treatment.